Toxic effects of realgar transforming solution on the reproduction of Caenorhabditis elegans. Issue 1 (2nd January 2018) - Liu, Dongling; Zhi, Dejuan; Wang, Mengqi; Bai, Yanli; Gao, Chunhong; Gao, Jiangli; Tian, Jing; Wang, Dong; Li, Hongyu
ABSTRACT: Realgar transforming solution is an arsenic formulation which has shown anticancer effects with low toxicity both in vivo and in vitro . In this study, Caenorhabditis elegans was used to evaluate its reproductive toxicity and its possible mechanisms. Realgar transforming solution decreased the brood size and induced proliferation arrest and apoptosis significantly only at an elemental concentration of 37.5 mg/L, while arsenic trioxide reduced the brood sizes and induced proliferation arrest and apoptosis of both the wild type N2 and let-60 ras(gf) mutant worms in an arsenic concentration dependent manner. Mitogen-activated protein kinase and protein p53 pathways may be involved in reproductive toxicity as evidenced by real-time quantitative polymerase chain reaction, RNA interference, and inhibition experiments with mitogen-activated protein kinases and p53. In conclusion, realgar transforming solution at the low arsenic (As) concentrations showed lower reproductive toxicity than arsenic trioxide, and a different molecular mechanism of reproductive toxicity is suggested.